SMO-Based Sensorless Control of a Permanent Magnet Synchronous Motor - Liu, Xin; Wang, Zhiwei; Wang, Wenzhuo; Lv, Yunling; Yuan, Bo; Wang, Shijie; Li, Wujing; Li, Qiufang; Zhang, Qiwen; Chen, Qianchang (Frontiers in Energy Research, 2022)
In order to reduce the chattering caused by the discontinuity of the control function in the traditional sliding mode observer (SMO), this article proposes a sliding mode observer with phase-locked loop (PLL) to estimate the speed and position of the rotor. The back electromotive force (EMF) of a permanent magnet synchronous motor (PMSM) in a static coordinate system is accurately estimated by SMO, and then, PLL is constructed to combine the observed rotor position angle and back EMF to compensate the phase lag in angle estimation so as to obtain a more accurate speed. It solves the problems of poor robustness and complex algorithms in the traditional SMO prediction algorithm. The simulation results show that the SMO with PLL can effectively reduce the system chattering and effectively improve the accuracy of rotor speed and position estimation.